MANAGEMENT OF INTELLECTUAL PROPERTY RIGHTS IN EDUCATIONAL INSTITUTIONS - Pranav Anand Ojha (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2023)
Mind is the greatest of all gift bestowed upon man. It is the source of all imaginations and creativity. By application of this imagination and creativity on the resources surrounded him; man has created its own world to fulfil his mental and physical need and comfort. Earlier, these creations by men were not his private but the public properties. But later, on the realization of commercial significance of these creations of human mind, the need was felt to protect and restrict the exploitation of such inventions and creations. And that is how; this concept of Intellectual Property Right came. Behind every creation, time, money, knowledge, efforts, and energy is required. It can take few minutes to years to create an intellectual property. These all together, costs huge investment on the part of creator[1]. And this requires due respect and recognition to those, who made the creation possible, this requirement is fulfilled in terms of IPR. Recognition or respect alone will not sufficient, there always is a need of motivation. So IPR acts as the incentive to the creator and encourage creativity and inventions but not only this, it also creates a healthy competition among the creators which is very important for the development of the society[2]. IPRs reward for the creativity and genuineness and ensure commercial gain for the creator or owner. This also helps in finding solutions for emerging issues and for more viable options. IPRs ensure the originality and genuineness of the article or products. IPRs are important factor to stimulate economic growth and competition in market.[3] [1]Dushyant Sharma, Intellectual Property and Need to Protect it, 9 Indian J. Sci. Res. 084(2014) [2]Id. [3] All Answers ltd, Importance of intellectual property rights, UKEssays.com (Apr. 14, 2020, 11:30 PM), https://www.ukessays.com/essays/property/importance-of-intellectual-property-rights.php?vref=1